Interviewer Effects in the European Social Survey - Koen Beullens; Geert Loosveldt (Survey Research Methods, 2016)
In this paper, we focus on interviewer effects in the European Social Survey, and seek to demonstrate that academic publications seldom take these effects into consideration. An analysis is provided of interviewer effects for 48 continuous items, covering 36 countries in six rounds. The analysis does not only deal with the means of variables. Using multilevel covariance structure analysis, interviewer effects on the relationships between these variables is also assessed. Results indicate that first, countries showing considerable interviewer effects regarding means are also more at risk regarding regression coefficients and second, ignoring interviewer effects leads to an overestimation of the effect size of the relationships between variables and an underestimation of standard errors.